Tolerability and activity of ublituximab, umbralisib, and ibrutinib in patients with chronic lymphocytic leukaemia and non-Hodgkin lymphoma: a phase 1 dose escalation and expansion trial. Issue 2 (February 2019) - Nastoupil, Loretta J; Lunning, Matthew A; Vose, Julie M; Schreeder, Marshall T; Siddiqi, Tanya; Flowers, Christopher R; Cohen, Jonathon B; Burger, Jan A; Wierda, William G; O'Brien, Susan; Sportelli, Peter; Miskin, Hari P; et al.
Summary: Background: Therapeutic approaches for B-cell malignancies continue to evolve, especially with regard to combination approaches. We assessed the safety and efficacy of the triplet ublituximab, umbralisib, and ibrutinib in patients with advanced B-cell malignancies. Methods: We did an open-label, phase 1 study with dose-escalation and dose-expansion phases, at five centres in the USA. Eligible patients were aged 18 years or older with histologically confirmed lymphocytic leukaemia or relapsed or refractory B-cell non-Hodgkin lymphoma, had measurable disease, adequate organ function, and an Eastern Cooperative Oncology Group (ECOG) performance status of 2 or less. Patients with known CNS lymphoma, active hepatitis B or C infection, or HIV were excluded. In the dose-escalation cohort, patients were treated in cycles of 28 days with escalating doses of oral umbralisib (400, 600, or 800 mg) and fixed doses of intravenous ublituximab (900 mg) and oral ibrutinib (420 mg for patients with chronic lymphocytic leukaemia; 560 mg for patients with B-cell non-Hodgkin lymphoma) in a standard 3 × 3 design until disease progression or intolerance. In the dose-expansion phase, patients were given the recommended dose of the drug combination as determined from the dose-escalation phase. The primary endpoints were safety, dose-limiting toxicities, and the maximum tolerated dose of umbralisib, when given in combination with ublituximab and ibrutinib. Safety was assessed in patients who received at least one dose of study drug; activity was assessed in all patients who had at least one post-treatment efficacy measurement. The study is ongoing but no longer recruiting patients. This trial is registered withClinicalTrials.gov, numberNCT02006485 . Findings: Between Sept 2, 2014, and Nov 6, 2017, we enrolled 46 patients: 24 in the dose-escalation cohort (n=14 chronic lymphocytic leukaemia or small lymphocytic lymphoma; n=10 B-cell non-Hodgkin lymphoma) and 22 in the dose-expansion cohort (n=9 chronic lymphocytic leukaemia or small lymphocytic lymphoma; n=13 B-cell non-Hodgkin lymphoma). 46 patients received at least one dose of study drug. The maximum tolerated dose of umbralisib was not reached. The recommended dose for the dose-expansion phase was umbralisib 800 mg orally once daily plus ibrutinib orally once daily and intravenous ublituximab 900 mg administered on days 1, 8, and 15 of cycle 1, day 1 of cycles 2–6, and on day 1 of cycles 9 and 12. 37 (84%) of 44 patients achieved an overall response (complete or partial response). The most common any-grade adverse events were diarrhoea (n=27 [59%]), fatigue (n=23 [50%]), infusion-related reaction (n=20 [43%]), dizziness (n=17 [37%]), nausea (n=17 [37%]), and cough (n=16 [35%]). Grade 3–4 adverse events were manageable with the most common being neutropenia (n=10 [22%]) and cellulitis (n=6 [13%]). Serious adverse events occurred in 11 (24%) of 46 patients and included rash (n=2 [4%]), pneumonia (n=2 [4%]), atrial fibrillation (n=2 [4%]), sepsis (n=2 [4%]), abdominal pain (n=1 [2%]), syncope (n=1 [2%]), cellulitis (n=1 [2%]), pneumonitis (n=1 [2%]), headache (n=1 [2%]), lung infection (n=1 [2%]), skin infection (n=1 [2%]), pleural effusion (n=1 [2%]), pericardial infusion (n=1 [2%]), upper gastrointestinal bleeding (n=1 [2%]), diarrhoea (n=1 [2%]), and weakness (n=1 [2%]). No deaths related to adverse events occurred. Interpretation: The combination of ublituximab, umbralisib, and ibrutinib seems to be tolerable and is associated with encouraging activity in advanced chronic lymphocytic leukaemia and B-cell non-Hodgkin lymphoma. This triplet combination will require further investigation in future studies to improve understanding of this novel, chemotherapy-free triplet combination in the management of these cancers. Funding: TG Therapeutics.